An Improved Surgical Technique to Increase Neck Width of Elastase-Induced Aneurysm Model in Rabbits: A Prospective Study - Zhang, Yang; He, Yu; Tang, ChaoJie; Wu, YuFan; Gu, Yi; Gu, BinXian; Chen, Li; Gao, WenWei; Zhou, ZhiGuo; Qi, YouKe; Mao, FaJiang; Sun, YongNing; et al. (Frontiers in Neurology, 2022)
Background Rabbit elastase-induced aneurysms have widely been used to test various endovascular materials over the past two decades. However, wide-necked aneurysms cannot be stably constructed. Objective The purpose of the study was to increase neck width of elastase-induced aneurysm model in rabbits via an improved surgical technique with two temporary clips. Materials and methods Fifty-four elastase-induced aneurysms in rabbits were successfully created. Group 1 (n=34) composed cases in which two temporary aneurysm clips were placed closely medially and laterally to the origin of right common carotid artery (RCCA), respectively. Group 2 (n=20) included cases in which a single temporary aneurysm clip was placed crossed the origin of RCCA. Digital subtraction angiography was performed before and immediately after elastase incubation and three weeks later. The diameter of the origin of RCCA before and immediately after elastase incubation and aneurysm sizes of two groups were measured and compared. Moreover, the correlation analysis was performed between the diameter of the origin of RCCA immediately after elastase incubation and aneurysm neck width. Results The mean aneurysm neck and dome width of group 1 was both significantly larger than that of group 2 (P < 0.001 and P = 0.005, respectively). Moreover, the proportion of wide-necked aneurysms (neck width ≥4 mm) in group 1 was significantly larger than that in group 2 (P = 0.004) and the mean D/N of group 1 was smaller than that of group 2 (P = 0.008). Furthermore, there was positive correlation between the diameter of the origin of RCCA immediately after elastase incubation and aneurysm neck width. Conclusions The improved surgical technique with two temporary clips, focusing on the direct contact of elastase with the origin of RCCA, could increase the neck width of elastase-induced aneurysm models in rabbits.